CuS2‐Passivated Au-Core, Au3Cu-Shell nanoparticles analyzed by Atomistic-Resolution Cs-Corrected STEM - Khanal, Subarna; Casillas, Gilberto; Bhattarai, Nabraj; Velázquez Salazar, J. Jesús; Santiago, Ulises; Ponce, Arturo; Mejía Rosales, Sergio; Yacamán, Miguel José (2013)
Au-core, Au3Cu-alloyed shell nanoparticles passivated with CuS2 were fabricated by the polyol method, and characterized by Cs-corrected scanning transmission electron microscopy. The analysis of the high-resolution micrographs reveals that these nanoparticles have decahedral structure with shell periodicity, and that each of the particles is composed by Au core and Au3Cu alloyed shell surrounded by CuS2 surface layer. X-ray diffraction measurements and results from numerical simulations confirm these findings. From the atomic resolution micrographs, we identified edge dislocations at the twin boundaries of the particles, as well as evidence of the diffusion of Cu atoms into the Au region, and the reordering of the lattice on the surface, close to the vertices of the particle. These defects will impact the atomic and electronic structures, thereby changing the physical and chemical properties of the nanoparticles. On the other hand, we show for the first time the formation of an ordered superlattice of Au3Cu and a self-capping layer made using one of the alloy metals. This has significant consequences on the physical mechanism that form multicomponent nanoparticles.